PENGEMBANGAN MEDIA PEMBELAJARAN MENULIS KARYA ILMIAH SISWA KELAS XI SMK - Salman Alade (Kantor Bahasa Provinsi Maluku Utara, 2021)
This study aims to design and develop learning media for writing scientific papers for vocational students. The theory used in this research is the theory of scientific writing learning, development of learning media, participatory learning, and collaborative learning. The method of this research is a development method with the implementation procedures based on 4D stages to develop learning tools consisting of four main stages, namely definition, design, development, and deployment. The design of learning media for writing scientific papers for vocational students is macromedia flash which includes three main contents, namely general aspects, media content, and aspects of learning media display. The results show that based on product trials, the development of learning media for writing scientific papers for SMK students has been proven to be effective in learning to make students able to write scientific papers